Kinetics of Heterogeneous Reaction of H2O2 and SO2 on Coal Fly Ash: Temperature Effect and Their Synergistic Effects - Zhou, Li; Lei, Ting; Kang, Dongjuan; Guo, Yucong; Zhang, Yunhong; Yang, Fumo; Ge, Maofa; Wang, Weigang (Frontiers in Environmental Science, 2022)
Coal-derived fly ash is a major aerosol composition in the atmosphere and presents a major challenge in understanding atmospheric environment. In this study, the heterogeneous uptake of hydrogen peroxide and sulfur dioxide on coal fly ash were investigated using Knudsen cell reactor coupled with a quadrupole mass spectrometer. The uptake coefficients were measured as a function of the initial mixing ratio of H2O2 and SO2 from 10 ppbv to 60 ppbv and the temperature dependence of the uptake coefficients were also carried out over a range from 253 K to 313 K. The mixing ratio of H2O2 and SO2 showed little effect on the uptake coefficients for these heterogeneous processes. As a function of temperature, the initial uptake coefficients of H2O2 and SO2 on coal fly ash were (0.48-1.65)×10-4 and (1.50-8.54)×10-5, respectively decreased with increasing temperature. The steady state uptake coefficients of H2O2 on coal fly ash was in the range of 2.46×10-5- 4.84×10-5, which increased with increasing temperature. Furthermore, we examined the synergistic effects between SO2 and H2O2 in their reaction on coal fly ash and found the existence of gaseous H2O2 appeared to enhance the ability of SO2 uptake on coal fly ash. Therefore, this finding suggests that the oxidation of SO2 on the surface of coal fly ash by gaseous H2O2 would promote SO2 consumption and transformation.